The effects of an increased calorie breakfast consumed prior to simulated match-play in Academy soccer players. Issue 7 (9th August 2017) - Briggs, Marc A.; Harper, Liam D.; McNamee, Ged; Cockburn, Emma; Rumbold, Penny L.S.; Stevenson, Emma J.; Russell, Mark
Abstract: Dietary analysis of Academy soccer players highlights that total energy and carbohydrate intakes are less than optimal, especially, on match-days. As UK Academy matches predominantly kick-off at ∼11:00 h, breakfast is likely the last pre-exercise meal and thus may provide an intervention opportunity on match-day. Accordingly, the physiological and performance effects of an increased calorie breakfast consumed ∼135-min before soccer-specific exercise was investigated. English Premier League Academy soccer players ( n = 7) repeated a 90-min soccer match simulation on two occasions after consumption of habitual (B hab ; ∼1100 kJ) or increased (B inc ; ∼2100 kJ) energy breakfasts standardised for macronutrient contributions (∼60% carbohydrates, ∼15% proteins and ∼25% fats). Countermovement jump height, sprint velocities (15-m and 30-m), 30-m repeated sprint maintenance, gut fullness, abdominal discomfort and soccer dribbling performances were measured. Blood samples were taken at rest, pre-exercise, half-time and every 15-min during exercise. Although dribbling precision ( P = .522; 29.9 ± 5.5 cm) and success ( P = .505; 94 ± 8%) were unchanged throughout all time-points, mean dribbling speed was faster (4.3 ± 5.7%) in B inc relative to B hab ( P = .023; 2.84 vs 2.75 m s −1 ). Greater feelings of gut fullness (67 ± 17%, P = .001) were observed in B inc without changes in abdominal discomfort ( P = .595). All other physical performance measures and blood lactate and glucose concentrations were comparable between trials (all P > .05). Findings demonstrate that Academy soccer players were able to increase pre-match energy intake without experiencing abdominal discomfort; thus, likely contributing to the amelioration of energy deficits on match-days. Furthermore, whilst B inc produced limited benefits to physical performance, increased dribbling speed was identified, which may be of benefit to match-play.